Distance Education.A system view, Michael Moore, Greg Kearsley : Wadsworth Publishing Company. ISBN: 0-534-26496-4 - Gorga, Gladys (2002)
This text introduces comprehensively the reader to the distance teaching/learning process. With this purpose, it presents a model of the Distance Education System to be used for understanding its embedded elements: contents, instructional design, communications, interaction, learning environment, and administration.